If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4y + -15 = 9 Reorder the terms: -15 + -4y = 9 Solving -15 + -4y = 9 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + -4y = 9 + 15 Combine like terms: -15 + 15 = 0 0 + -4y = 9 + 15 -4y = 9 + 15 Combine like terms: 9 + 15 = 24 -4y = 24 Divide each side by '-4'. y = -6 Simplifying y = -6
| (1/2)(x+20)=4 | | -7=-2v-1 | | -(4x-2)=-6+12x | | 12x-(3+4x)= | | 0=-8y-26 | | 14=-8u+18 | | -1/2+5/12x=2/3x-3/4 | | -7u+22=0 | | 0=-5x+40 | | 6x+2=-6 | | 0.58-0.38= | | 0=-6v-22 | | -5v-17=-8 | | 0=-5y+15 | | -15=7v-14 | | 4(2y+1)=-2(y-12) | | 11=-2w-5 | | 6n+4-2=3n+6 | | 2z+13=19 | | -3u+18=0 | | -6(-7+-9f+7y)= | | -8-2(3-x)=0 | | 9x+6.52=5x+12 | | -20f+2(f-4f)=52 | | 16=-2t | | 6(a-5)+6=4(a-4) | | 4-m/5=11 | | 9y-4y=3 | | 3(x-1)-2(x^2+2x+3)-5(x+6)=0 | | 6x=2000 | | 4x=-2.2 | | (5*x+7)/(3x)-(2x-2)/(3x) |